Pengaruh Tanah Liat Terhadap Penyerapan Air Hujan Pada Tanaman - Lola Sri Wahyuni Halawa; Dilva Dwi Wulan Halawa; Julvan Ndruru (CV. SINAR HOWUHOWU, 2026)
This study aims to explore the effect of clay soil on rainwater absorption and plant growth. Using a factorial experimental design, this research compares the ability of clay soil and sandy soil to retain water and support the growth of rice, corn, and vegetable crops. The results show that clay soil has a higher water retention capacity, with an average moisture content of 30% after simulated rainfall, compared to 15% in sandy soil. Plants grown in clay soil exhibited better growth, with an average height of 45 cm, 12 leaves per plant, and a dry weight of 40 grams, compared to 30 cm, 7 leaves, and 25 grams in sandy soil. These findings highlight the importance of soil type selection in sustainable agriculture practices, with clay soil serving as a more efficient growing medium in improving water availability and supporting plant growth.